A new nephelometric assay for β-trace protein (prostaglandin D synthase) as an indicator of liquorrhoea. Issue 3 (1st September 2001) - Petereit, H F; Bachmann, G; Nekic, M; Althaus, H; Pukrop, R
Abstract : OBJECTIVES: To determine the sensitivity and specificity of a nephelometric β-trace protein assay for the diagnosis of liquorrhoea. METHODS: One hundred and forty clinical samples with suspected liquorrhoea were analysed by a newly developed nephelometric assay. An established electroimmunoassay served as a reference method. The sensitivity and specificity of the β-trace nephelometric assay were calculated by a 2x2 contingency table for 10 different versions of a dichotomised nephelometric variable. In 52 patients (79 samples), the nephelometric findings were validated by referring to the clinical diagnosis based on the course of the disease, imaging techniques, and surgical inspection. RESULTS: Given a specificity of 100%, a β-trace protein concentration of 6 mg/l or higher in a sample indicated liquorrhoea with a sensitivity of 92% compared with the reference method and of 93% compared with the clinical evaluation. The relation between the electroimmunoassay and the nephelometric assay was highly significant (p<0.001). CONCLUSIONS: The nephelometric β-trace protein assay is a simple and rapid method for the detection of liquorrhoea with high sensitivity and specificity and may facilitate the diagnosis of fistulas leaking CSF.